2017
DOI: 10.7860/jcdr/2017/27287.10421
|View full text |Cite
|
Sign up to set email alerts
|

Eye Donation Awareness and Conversion Rate in Hospital Cornea Retrieval Programme in a Tertiary Hospital of Central India

Abstract: Introduction: Corneal blindness accounts for 6-8 million blinds in the world. In India, it is estimated that there are approximately 6.8 million people who have vision less than 6/60 in at least one eye due to corneal diseases. Aim:This study was done to assess the awareness about eye donation amongst attendants of critically ill and deceased patients, their willingness to donate eyes, the efficacy of grief counselling by Eye Donation Counsellors (EDC), its impact on the conversion rate and the reasons for poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“…74 , 75 Sharma et al conducted a prospective study in which grief counselors identified 554 critically ill patients and discussed the topic of eye donation with their families. 76 In a follow up survey, the grief counselors had the largest influence on the decision to donate. In a separate pilot intervention, counselors from a regional eye bank were notified of every hospital death and reached out to the next of kin to discuss the possibility of eye donation.…”
Section: Introductionmentioning
confidence: 99%
“…74 , 75 Sharma et al conducted a prospective study in which grief counselors identified 554 critically ill patients and discussed the topic of eye donation with their families. 76 In a follow up survey, the grief counselors had the largest influence on the decision to donate. In a separate pilot intervention, counselors from a regional eye bank were notified of every hospital death and reached out to the next of kin to discuss the possibility of eye donation.…”
Section: Introductionmentioning
confidence: 99%
“…Source of motivation for corneal donation was counselling in a study by Acharya, et al in which about 41% participants were willing to donate cornea after counselling [13]. Sharma, et al in their study observed 61 (57.5%) cases where the willingness come post direct motivation by grief counselors [6]. Yew, et al concluded that imparting proper knowledge about eye donation can increase the corneal retrieval [14].…”
Section: Discussionmentioning
confidence: 99%
“…The effective treatment with high success rate in restoring sight among patients with corneal blindness include corneal transplantation.National Programme for control of blindness (NPCB), initiated by Government of India through its continuous efforts tried to reduce the backlog of preventable corneal blindness through comprehensive eye care services, including corneal transplantation [5]. However, even after increasing awareness of corneal donation, the number of donors remains much lower and also waiting period for corneal transplantation remains high at most hospitals across the country [6]. Apart from the efforts of increasing awareness, the Eye Bank Association of India also made efforts to increase the corneal procurement rate over several years.…”
Section: Introductionmentioning
confidence: 99%
“…que impulsiona os pacientes a submeterem-se a cirurgia 12,13,27,28 . Contudo, estima-se que cerca de 53% da população necessitada não tenha acesso ao TC 28 , principalmente porque que as taxas de doação de córnea não acompanham a demanda crescente pelo TC [29][30][31] .…”
Section: Introductionunclassified
“…Logo, estudos epidemiológicos são necessários para mapear a situação da oferta e da demanda pelo TC no Brasil, apontar deficiências e dificuldades a serem superadas, divulgar a importância da notificação de potenciais doadores e discutir estratégias para aumentar a conversão desses em doadores efetivos, a fim de reduzir as filas de espera por TC [29][30][31] .…”
Section: Introductionunclassified